Surgical treatment of periimplantitis using a bone substitute with or without a resorbable membrane: a prospective cohort study - Ann-Marie Roos-Jansa°ker (Blackwell Synergy, 2007)
Objectives: The aim of this prospective cohort study was to compare two regenerative surgical treatment modalities for peri-implantitis. Material and Methods: Thirty-six patients having a minimum of one osseointegrated implant, with a progressive loss of bone amounting to X3 threads (1.8 mm) following the first year of healing, combined with bleeding and/or pus on probing, were involved in this study. The patients were assigned to two different treatment strategies. After surgical exposure of the defect, granulomatous tissue was removed and the infected implant surface was treated using 3% hydrogen peroxide. The bone defects were filled with a bone substitute (Algipores). In 17 patients (Group 1), a resorbable membrane (Osseoquests) was placed over the grafted defect before suturing. In 19 patients (Group 2), the graft was used alone. Results: One-year follow-up demonstrated clinical and radiographic improvements. Probing depths were reduced by 2.9mm in Group 1 and by 3.4mm in Group 2. Defect fill amounted to 1.5 and 1.4 mm, respectively. There was no significant difference between the groups. Conclusion: It is possible to treat peri-implant defects with a bone substitute, with or without a resorbable membrane.